ABOUT THE DRAFT LAW ON GENERAL ADMINISTRATIVE PROCEDURE - Step forward or ten steps aside? - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Serbia, as a member of the former Yugoslavia, has Administrative procedure Act since 1930. This Law has been made under the model of Austrian Administrative Procedure Act of 1925. This Law has been verified through praxis of almost one century. Lately, Serbian Ministry of Justice and State’s Administration prepared Draft Law on Administrative Procedure which is totally different from existing Law. Draft Law is combination of the rules taken from the new Croatian Administrative Procedure Act of 2010, which is far from being verified in praxis. On the other side, Draft is full of disputable theoretical definitions, which makes this text similar to "scientific" article or book. Existing Administrative Procedure Act is in all senses much better than the Draft. With some minor changes this Law would be perfect and could be used easily in the praxis. The Draft would cause a lot of problems, make confusion and demand a lot of time in order to prepare civil servants to understand and implement this Law. That is all unnecessary! All this reasons make this author to come to the conclusion that this is not a step forward. This is neither step back, because we never had such bad law in the past. This is ten steps aside!